Aportación al conocimiento fenológico de las rodofíceas marinas de la playa de Guarajuba (Camaçari, Bahia) Brasil - Magalhães Lucio, Adriana; De Castro Nunes, José Marcos (Botanica Complutensis, 2002)
LUCIO, A. M. & NUNES, J. M. DE C. 2002. Contribution of the fenologyc knowledge of marine Red algae of the Guarajuba beach, (Camaçari, Bahia) Brazil. Bot. Complutensis 26: 17-34. On a study of the marine benthic red algae of the Guarajuba beach, 41 species were identified. For the present study, the fenology, habitat, frequency, seasonality and epiphytic relationship of the species were analysed. The reef’s frontal region and the reef`s plato have shown a bigger richness of species along the year, with 35 and 30 species, respectively. The genus Gracilaria (6 species) was the best representative one. A 70% of the species have shown reproductive structures, and the tetrasporic ones were more frequently. Generally, Guarajuba beach has shown more fertile algae than the oceanic border of Salvador city. Gelidium torulosum Kützing was recorded in the first time for the Bahia State and Petroglossum undulatum C.W. Schneider was recorded to the Brazilian northern littoral.